Research progress on positron emission tomography using radionuclide-labeled fibroblast activation protein inhibitor in diagnosis of cardiac diseases - JIA Yingqi, ZHANG Min, LI Biao (Zhenduanxue lilun yu shijian)
Fibroblast activation protein (FAP) is a type Ⅱ transmembrane serine protease specifically expressed on the surface of activated cardiac fibroblasts (CFs). During myocardial injury, inflammation, and fibrosis, it drives myocardial interstitial remodeling and collagen deposition by degrading the extracellular matrix and activating key pathways such as transforming growth factor-β (TGF-β), thus serving as a central effector target in the development of myocardial fibrosis. FAP is significantly upregulated exclusively in activated CFs, with minimal expression in normal myocardial tissue, provi-ding a molecular basis for the non-invasive and precise diagnosis of cardiac diseases. In recent years, radionuclide-labeled FAP inhibitor (FAPI) positron emission tomography (PET), with its non-invasiveness, high targeting specificity, and quantitative evaluation capability, has enabled the early detection of microfibrosis signals at the molecular level. This technique overcomes the reliance of conventional imaging (e.g., cardiac magnetic resonance) on structural changes, demonstrating unique advantages in the dynamic evaluation of active myocardial fibrosis and providing a novel pathway for early diagnosis, exploration of pathological mechanisms, and prognostic evaluation of cardiac diseases. Current research confirms that FAPI-PET holds significant application value across multiple cardiac diseases. For example, in left ventricular remodeling after acute myocardial infarction, dynamic monitoring of FAP activity in the peri-infarct zone can predict ventricular dilation and adverse remodeling trends. In cardiotoxicity induced by radiotherapy, chemotherapy, or immunotherapy, it achieves early warning of subclinical fibrosis. For cardiac amyloidosis, it facilitates early quantification of myocardial fibrotic burden and assists in risk stratification and prognosis evaluation across different subtypes. In pulmonary hypertension and right ventricular remodeling, it can comprehensively evaluate diffuse fibrosis and reflect the severity of the di-sease. For different subtypes of cardiomyopathy (e.g., hypertrophic/dilated), it assists in clinical phenotype identification by analyzing the spatial distribution of fibrosis. Additionally, it can be used to evaluate the atrial injury repair responses after catheter ablation for atrial fibrillation, thereby predicting the risk of arrhythmia recurrence. This study reviews domestic and international research advances in the application of FAPI-PET in the diagnosis of cardiac diseases, and discusses its application potential and future challenges.